Fast measurement method of defocused differential correlation-confocal microscopy. (January 2023) - Li, Rongji; Ma, Han; Li, Angze; Zhao, Weiqian; Qiu, Lirong
Highlights: Reduces the scanning time and data storage space of 3D topographic imaging. Measuring height is unaffected by the sample reflectivity. A novel alternative approach with higher lateral resolution level as conventional method. Applied directly to existing confocal microscopy. Abstract: Confocal microscopy (CM) is extensively used in many fields due to its unique axial tomographic capabilities and high-resolution three-dimensional imaging properties. However, this requires layer-by-layer scanning on the sample along the axial direction, which restricts the imaging speed. In this study, we have proposed the defocused differential correlation confocal microscopy (DDCCM), which is based on axial sensing imaging and correlation product method. This method can obtain an axial response curve independent of sample reflectivity and fast 3D sensing imaging of the sample by dividing the difference between the two defocused intensity images by their sum, improving the imaging efficiency at least five times higher than that of CM. The proposed method improves the lateral resolution using the correlation product of two defocused intensity images. DDCCM provides a new way for the fast measurement of conventional CM without changing the system conditions.